2021
DOI: 10.3390/ijerph18105111
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy towards COVID-19 Vaccines: An Analytical Cross–Sectional Study

Abstract: Vaccination is the most promising strategy to counter the spread of Coronavirus Disease 2019 (COVID-19). Vaccine hesitancy is a serious global phenomenon, and therefore the aim of this cross-sectional study was to explore the effect of educational background, work field, and social media on attitudes towards vaccination in Jordan. We compared between medical personnel who were in direct contact with patients and non-medical individuals at Jordan University Hospital in terms of demographics, knowledge about COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 40 publications
4
60
1
Order By: Relevance
“…The major factors to vaccine hesitancy in our study population include concerns about serious vaccine reactions and side effects and doubts on vaccine efficacy. The findings are consistent with data from other countries reporting similar reasons of hesitancy [12][13][14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The major factors to vaccine hesitancy in our study population include concerns about serious vaccine reactions and side effects and doubts on vaccine efficacy. The findings are consistent with data from other countries reporting similar reasons of hesitancy [12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…Pregnant women need to discuss with their doctors before getting COVID-19 vaccine as yet the vaccines have not been tested in pregnant women [1,2,[6][7][8]. Current guidelines suggest that people previously infected with COVID-19 still need to be vaccinated as there are chances of reinfection and it is also observed that people who have been vaccinated after having COVID-19 infection have observed a strong immune reaction after the first of the two shots with the Pfizer and Moderna vaccines [7][8][9][10][11][12][13]. Vaccine hesitancy is a major challenge to bring an end to this pandemic in countries like Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the efficacy of the voluntary mass COVID-19 vaccinations coordinated by the Polish government [ 20 ] may prove significantly limited, as a significant part of the Polish society remains vaccination skeptics [ 21 ], and the promotion of vaccination is unsatisfactory [ 22 ]. High levels of vaccination hesitancy is common among societies all around the world that belong to different cultural backgrounds such as Germany [ 23 ], Spain [ 24 ], Israel [ 25 ], Jordan [ 26 ], and Japan [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…During our survey, infection rates (ranging from 83/10,000 in the beginning to 57/10,000 in the middle and to 64/10,000 at the end of February in Germany) [ 10 ] were lower than in December 2020 by up to 200/100,000. Recent, partially not-yet-peer-reviewed surveys of HCWs have shown vaccine acceptance rates between 31% and 86% [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] ( Table S1 ). However, most of these studies had lower numbers of participants, were performed in single working groups or had fewer items, thereby providing descriptions of reasons for hesitancy that were lacking in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Associated factors mainly were lack of trust in new vaccines, efficacy and safety; fear of side effects; not feeling well informed; safety concerns; and the velocity of the development process. Additionally, only a few studies from Germany existed when we began, and they did not cover large numbers of HCWs from all German regions [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%